Development Of A Secure Model For Mobile Government Applications In Jordan - Ala’a Saeb Al-Sherideh; Roesnita Ismail; Mohammad Rasmi Al-Mousa; Khaled Al-Qawasmi; Ala'a Al-Shaikh; Hebatullah Awwad; Khaled Maabreh; Mohammad Alauthman (Elsevier, 2024)
Indexed by Scopus